PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION DI KELAS V.A SDN 44 KALUMBUK KOTA PADANG - Muhammad Nur (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2016)
ABSTRACT This research aims to increasing activity and the learning students using Realistic Mathematics Education (RME) approach. Objective of research covers students of classroom V.A SDN 44 Kalumbuk Kuranji District Padang City which are 30 students. This research is a classroom action research. This research was conducted on the first semester of year 2013/2014 in SDN 44 Kalumbuk Kuranji District Padang City. This research data was collected through observation, interview, note taking, video, documentation and test result. The result of data analysis showed that from oral activity, motoric, mental, and drawing the increasing from phase I to phase II. The same thing also happened on students learning outcomes, those are: (1) the average of students learning outcome of phase I is 73, 83 and it became 91,16 on phase II. Based on the the result of the research by using RME on the study of mathematics can increase the quality of education in the future. Keywords: Activities of learning, Learning outcomes, RME